Augmented Reality in Engineering Education: Opportunities and Advantages - Aleksandr Nesterov; Ivan Kholodilin; Aleksandr Shishkov; Pavel Vanin (Communications - Scientific letters of the University of Zilina, 2017)
The article is dedicated to the study of the possibility of applying augmented reality technologies in the field of engineering education. The prerequisites for creation and development of Industry 4.0 are considered. The study considers the concept and the technology of augmented reality. The ground of relevance and timeliness of its application in the professional training education process of engineers from different industrial departments is given. The problems of engineering education are reflected. The modern tendencies of engineering education development are considered. The methods of augmented reality technology application in support for the education process are reflected upon. The advantages and disadvantages of augmented reality technologies’ usage in the engineering education are considered.